PENGARUH INTENSITAS PEMANFAATAN AI CHATBOT GENERATIF TERHADAP KEMANDIRIAN BELAJAR MAHASISWA TADRIS MATEMATIKA PADA ERA PEMBELAJARAN DIGITAL - Fidya Desi Aryani; Atika Helmalia; Erlika Nurul 'aini; Nalim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The utilization of Artificial Intelligence (AI)-based chatbots in education is steadily increasing and holds the potential to support student self-regulated learning. This study aims to determine the effect of AI chatbot usage intensity on the independent learning capabilities of Mathematics Education students. The research implemented a quantitative approach with a survey method involving 40 respondents. Data were gathered through a questionnaire using a five-point Likert scale, ranging from Strongly Agree, Agree, Neutral, Disagree, to Strongly Disagree. Prior to regression analysis, the data were subjected to classical assumption tests. The normality test results showed a Test Statistic value of 0.129 with a significance level of 0.091 (> 0.05), indicating that the data were normally distributed. The linearity test results revealed a significance value on Deviation from Linearity of 0.159 (> 0.05) and a significance value on Linearity of 0.000 (< 0.05), which confirms a linear relationship between the intensity of AI chatbot usage and student independent learning. Consequently, all prerequisites for regression analysis were fully met. The simple linear regression analysis findings demonstrated that the intensity of AI chatbot usage has a significant effect on the independent learning of Mathematics Education students, obtaining a regression coefficient value (β) of 0.417, a t-value = 4.261, and a coefficient of determination () of 0.323. These findings indicate that the intensity of AI chatbot usage contributes 32.3% to the variation in students' independent learning, suggesting that this platform can be optimized as a digital tool to enhance student independent learning in the digital era.